Analisis Kualitas Air Pada Tambak Udang Vaname CV. Putera Manggala Abadi, Desa Pagarawan - Dinata, Faldhi Dinata; Adibrata, Sudirman; Aisyah, Siti (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2024)
Vaname shrimp (Litopenaeus vannamei) is valued as a superior variety, however, knowing the parameters of water quality is needed, so the role of water is very important to pay attention to according to the needs of Vaname shrimp. The purpose of this study is to analyze the value of water quality parameters in the Vaname shrimp farming area which includes temperature, Total Suspendid Solid (TSS), pH, salinity, Dissolved Oxygen (DO), Biological Oxygen Demand (BOD) and ammonia in CV. Prince of Manggala Abadi. Analysis activities were carried out at three stations, namely Station I (Selindung river), Station II (shrimp pond) and Station III (pond wastewater). This research method uses the Storet method and wastewater holding capacity. The results of parameter measurements on the water quality of the three stations are in accordance with quality standards, namely temperature, Total Suspendid Solid (TSS), salinity, pH, Dissolved Oxygen (DO) and Biological Oxygen Demand (BOD). The results of water quality measurements that are not in accordance with quality standards, namely ammonia parameters. The calculation of river water quality status (Station I) using the Storet method shows a total score of -4. The results of calculating the status of wastewater quality using the carrying capacity of water pollution loads show BPA < BPM, where wastewater is still in accordance with quality standards. Regular measurement of water quality parameters can allow anticipating the impact on Vaname shrimp resulting in productivity levels. In overcoming fluctuations in environmental parameters, it is necessary to change water, pony, and administer probiotics periodically.